Integrated prodrug micelles with two-photon bioimaging and pH-triggered drug delivery for cancer theranostics. Issue 2 (4th November 2019) - Xu, Hong; Ma, Boxuan; Jiang, Jizhou; Xiao, Sutong; Peng, Rongrong; Zhuang, Weihua; Li, Gaocan; Wang, Yunbing
Abstract: Nanodrug carriers with fluorescence radiation are widely used in cancer diagnosis and therapy due to their real-time imaging, less side effect, better drug utilization as well as the good bioimaging ability. However, traditional nanocarriers still suffer from unexpectable drug leakage, unsatisfactory tumor-targeted drug delivery and shallow imaging depth, which limit their further application in cancer theranostics. In this study, an integrated nanoplatform is constructed by polymeric prodrug micelles with two-photon and aggregation-induced emission bioimaging, charge reversal and drug delivery triggered by acidic pH. The prodrug micelles can be self-assembled by the TP-PEI (DA/DOX)-PEG prodrug polymer, which consists of the two-photon fluorophore (TP), dimethylmaleic anhydride (DA) grafted polyethyleneimine (PEI) and polyethylene glycol (PEG). The PEG segment, DOX and DA are bridged to polymer by acid cleavable bonds, which provides the micelles a 'stealth' property and a satisfactory stability during blood circulation, while the outside PEG segment is abandoned along with the DA protection in the tumor acidic microenvironment, thus leading to charge reversal-mediated accelerated endocytosis and tumor-targeted drug delivery. The great antitumor efficacy and reduced side effect of these pH-sensitive prodrug micelles are confirmed by antitumor assays in vitro and in vivo . Meanwhile, these micelles exhibited great deep-tissue two-photon bioimaging ability up to 150 μm in depth. The great antitumor efficacy, reduced side effect and deep two-photon tissue imaging make the TP-PEI (DA/DOX)-PEG prodrug micelles would be an efficient strategy for theranostic nanoplatform in cancer treatment.